A Model of Unilateral Cerebral Anterior and Posterior Anastomotic Vein Occlusion in the Rat - Cokluk, C; Aydin, K; Korkmaz, A; Senel, A; Iyigun, O; Onder, A (Georg Thieme Verlag KG, 2005)
A new rat model of the sacrifice of the anterior and posterior cortical anastornotic veins by the microsurgical technique was used to evaluate venous infarction. 20 male Sprague-Dawley rats were used in this experiment. Small burr-holes were done over the anterior and posterior anastornotic veins. After the precise description of these vessels, bipolar coagulation and micro-scissor was used for sacrifice. Specimens were evaluated by histopathological techniques. Hemispheric swelling, midline shift, brain edema, subcortical petechial hemorrhage, infarction and necrosis were histopathological findings on the microscopic examination. Our results revealed that the sacrifice of the anterior and posterior anastornotic veins was a very successful model in the evaluation of brain damage after the disturbance to the venous circulation.
Keywords: Cerebral Veins; Anastomotic Veins; Brain Swelling; Venous Ischemia; Rat Venous Ischemia Model